Cryoballoon Versus Laserballoon: Insights From the First Prospective Randomized Balloon Trial in Catheter Ablation of Atrial Fibrillation. (February 2021) - Chun, Julian K.R.; Bordignon, Stefano; Last, Jana; Mayer, Lukas; Tohoku, Shota; Zanchi, Simone; Bianchini, Lorenzo; Bologna, Fabrizio; Nagase, Takahiko; Urbanek, Lukas; Chen, Shaojie; Schmidt, Boris
Abstract : Background: Pulmonary vein isolation (PVI) represents the cornerstone in atrial fibrillation ablation. Cryoballoon and laserballoon catheters have emerged as promising devices but lack randomized comparisons. Therefore, we sought to compare efficacy and safety comparing both balloons in patients with persistent and paroxysmal atrial fibrillation (AF). Methods: Symptomatic AF patients (n=200) were prospectively randomized (1:1) to receive either cryoballoon or laserballoon PVI (cryoballoon: n=100: 50 paroxysmal atrial fibrillation + 50 persistent AF versus laserballoon: n=100: 50 paroxysmal atrial fibrillation + 50 persistent AF). All antiarrhythmic drugs were stopped after ablation. Follow-up included 3-day Holter-ECG recordings and office visits at 3, 6, and 12 months. Primary efficacy end point was defined as freedom from atrial tachyarrhythmia between 90 and 365 days after a single ablation. Secondary end points included procedural parameters and periprocedural complications. Results: Patient baseline parameters were not different between both groups. In all (n=200) complete PVI was obtained and the entire follow-up accomplished. Balloon only PVI was obtained in 98% (cryoballoon) versus 95% (laserballoon) requiring focal touch-up in 2 and 5 patients, respectively. Procedure but not fluoroscopy time was significantly shorter in the cryoballoon group (50.9±21.0 versus 96.0±20.4 minutes; P <0.0001 and 7.4±4.4 versus 8.4±3.2 minutes, P =0.083). Overall, the primary end point of no atrial tachyarrhythmia recurrence was met in 79% (cryoballoon: 80.0% versus laserballoon: 78.0%, P =ns). No death, atrio-esophageal fistula, tamponade, or vascular laceration requiring surgery occurred. In the cryoballoon group, 8 transient but no persistent phrenic nerve palsy were noted compared with 2 persistent phrenic nerve palsy and one transient ischemic attack in the laserballoon group. Conclusions: Both balloon technologies represent highly effective and safe tools for PVI resulting in similar favorable rhythm outcome after 12 months. Use of the cryoballoon is associated with significantly shorter procedure but not fluoroscopy time.